Integrating Ethical, Legal, and Cultural Paradigms: Advancing Environmental Stewardship - BEREBON, Charles B. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
The escalating environmental challenges of the modern world demand a comprehensive understanding of humanity’s moral and legal responsibilities toward nature. Drawing upon Indian philosophical concepts of Dharma and Karma and Christian values, alongside contemporary debates on intrinsic and instrumental values of the environment, this study investigates the ethical frameworks underpinning environmental stewardship. The research critically evaluates India’s constitutional provisions and environmental laws, assessing their implementation and alignment with sustainable development goals. It also explores religious and cultural narratives, such as Judeo-Christian and Indian traditions, to highlight their role in shaping environmental ethics. Through a multidisciplinary lens combining philosophy, law, cultural studies, and environmental ethics, this research underscores the urgent need for an ecocentric worldview and ethical governance. This study contributes to the Environmental Humanities by advocating for an integrated ethical and legal approach to address ecological degradation and ensure justice for both human and non-human entities.